International student recruitment: benefits and globalisation to the university / S.F. Zakaria ... [et al.] - Zakaria, S.F.; Mamat, A.M.I.; Zakaria, Z.; Supar, A. (UiTM Press, 2024)
The internationalization of higher education has growing significance in Malaysia, with international student enrollment emerging as a pivotal element in this discourse. This paper assesses the impact of the government-to-government approach as recruitment strategies aimed at potential applicants, the direct financial benefits international students bring to the university and effectiveness of this recruitment strategy within the context of UiTM. The methodology used in this project was a descriptive approach. The research adopts a multidimensional framework encompassing various data sources, analyses, and evaluations. This study shows that student recruitment strategy through the government-to-government approach has a higher impact on student enrolment in comparison to other methods employed. This approach also creates avenues for potential collaborative endeavours across various departments within the university. It expands the prospects for collaborative research initiatives and opens doors to various other forms of cooperation. Over the course of the years 2021 to 2023, this initiative made a substantial contribution to the university’s revenue stream by generating a total of RM 683,107 in tuition fees. This study underscores the noteworthy financial impact of the initiative on the university’s financial sustainability, highlighting the potential implications and opportunities for further investigation in the field of higher education finance.